Dutch cultural standards from Czech perspective in academic environment - Straka, Martin; Křečková Kroupová, Zuzana, 1972-; Volfová, Jitka, 1982-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2023)
The Czech Republic and the Netherlands are countries of various similarities, whether it is the geographical proximity, EU membership or similarity in traditions. Similarities aside, there are significant differences when it comes to culture. These differences can lead to misunderstandings, cultural shock and unpleasant situations when foreign students come to the Netherlands to study at a Dutch university. To ease the study abroad and make the most out of it, it is key that students adapt to the foreign culture as quickly and as smoothly as possible. This bachelor thesis focuses on the cultural background and theory of each of these two countries and establishes the main Dutch cultural standards from the perspective of a Czech student based on qualitative research. Following the cultural standards are certain recommendations to aid the students who wish to study in the Netherlands with proper integration into the Dutch culture.
Vedoucí práce: Zuzana Křečková Kroupová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international business [obor bakal. práce]; bakalářské práce; bachelor's theses